Development and characterisation of ciprofloxacin hydrochloride solid lipid nanoparticles for ocular delivery - Dhege, Clarence (Rhodes University, Faculty of Pharmacy, Pharmacy)
Access restricted until April 2023.
Keywords: Uncatalogued